Ecological biological valuation of condition of pasture and hayfield pasture wegwtable communities of the Volga delta under the influence of anthropogenic factors - T. V. Dimova (Юг России: экология, развитие, 2015)
In the article we represent information about using of criteria of evaluation of the Volga delta of vegetation pastures and hayfield under the influence of pasture and mowing.